The Role of Mediators in Reducing Divorce Rates in Bantaeng Regency Religious Courts in 2019-2020 - Wahyuni Wahyuni; Rapung Rapung (Journal of Family Law and Islamic Court, 2022)
This project intends to 1) understand the function of mediators in reducing divorce rates, the success rate of mediation in 2019-2020, and the impediments to mediation. 2). Knowing how the Bantaeng Regency Religious Court's mediator carries out the procedure of adopting mediation. This sort of research employs descriptive qualitative methodologies, gathering data directly from the field to observe the item under investigation. Primary and secondary data sources were used to collect information. Primary data comes from field research involving interviews, and secondary data comes from books and official papers. Techniques for gathering data include recordkeeping and interviews. According to the study's findings, 1) the mediator's role in the success rate of mediation in divorce cases at the Bantaeng Regency Religious Court cannot be separated from the mediator's crucial function in enabling the parties. Although the success rate remains very low, it must be implemented because it is PERMA RI's mandate. 2). Mediation is used by the Bantaeng Regency Religious Court in compliance with RI PERMA NO 1/2016 protocols, and all cases that go to court are mediated beforehand. In 2019, just 2.56 percent of mediation cases were effectively mediated out of 39 cases; in 2020, as many as 6.25 percent of the 48 mediation cases entered were successful. While the overall number of divorce cases in 2019 was 342 and 410 in 2020, there were divorce cases that could not be negotiated. The mediation process is hampered by a) the absence of the parties and b) the passage of time. c). In bad faith mediation process d). Absence of parties e). The stipulations of the peace treaty were not followed.--Penelitian ini bertujuan untuk 1). Mengetahui bagaimana peran mediator dalam mengurangi angka perceraian, tingkat keberhasilan mediasi pada tahun 2019-2020, faktor penghambat 2). Mengetahui bagaimana praktik penerapan mediasi yang dilakukan oleh mediator Pengadilan Agama Kabupaten Bantaeng. Jenis penelitian ini menggunakan metode kualitatif deskriptif, dengan cara mengumpulkan data-data secara langsung turun kelapangan melihat objek yang diteliti. Sumber data yang diperoleh yaitu data primer dan sekunder. Data primer adalah d ata yang diperoleh melalui penelitian lapangan dengan wawancara, sedangkan data sekunder adalah data yang diperoleh melalui buku-buku, dan dokumen-dokumen resmi. Teknik pengumpulan data dengan cara dokumentasi dan interview. Berdasarkan hasil penelitian menunjukkan bahwa 1). Peran mediator terhadap tingkat keberhasilan mediasi dalam perkara perceraian di Pengadilan Agama Kabupaten Bantaeng tidak terlepas dari peranan penting seorang mediator dalam memfasilitasi para pihak. Walaupun tingkat keberhasilannya masih sangat rendah namun tetap harus dilaksanakan karena hal tersebut merupakan amanat PERMA RI. 2). Praktik penerapan mediasi di Pengadilan Agama Kabupaten Bantaeng sudah sesuai dengan prosedur PERMA RI NO 1 Tahun 2016 semua perkara yang masuk ke pengadilan akan di mediasi terlebih dahulu. Tingkat keberhasilan perkara mediasi di tahun 2019 hanya 2,56% yang berhasil di mediasi dari 39 perkara, pada tahun 2020 sebanyak 6,25% dari 48 jumlah perkara mediasi yang masuk. Sedangkan jumlah keseluruhan perkara perceraian pada tahun 2019 sebanyak 342 kasus dan pada tahun 2020 sebanyak 410, namun perkara perceraian tersebut ada yang tidak dapat dimediasi. Adapun faktor penghambat proses mediasi yaitu a). Ketidak hadiran para pihak b). Melewati batas waktu c). Proses mediasi dengan itikad tidak baik d). Kurangnya pihak e). Syarat kesepakatan damai tidak terpenuhi.